Wykorzystanie wybranych innowacyjnych rozwiązań zarządzania sferą bezpieczeństwa publicznego przez policję = Selected problems of innovative application solutionsin public safety management by the Police - Graczyk, Krzysztof; Tabaczniuk, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Application of informatics s and related innovative solutions in a broadly defined public safety has recently offered systems enabling identification, monitoring and prevention of potential threats. Creating hazard maps, also by the residents themselves, should be seen as an essential element of public safety management, as implemented in inter-institutional and social partnership.
Keywords: zarządzanie bezpieczeństwem publicznym; innowacje; mapy zagrożeń; public safety management; innovation; threat maps